2021
DOI: 10.1002/dad2.12198
|View full text |Cite
|
Sign up to set email alerts
|

Subtle cognitive impairment as a marker of Alzheimer's pathologies and clinical progression in cognitively normal individuals

Abstract: Introduction Subtle cognitive impairment (SCI) may appear before pathological changes surpass thresholds for abnormality. We aimed to investigate whether SCI could predict Alzheimer's pathologies and advancement. Methods A total of 816 cognitively normal individuals were enrolled to assess the longitudinal neuropathological and clinical correlates of baseline SCI, via linear mixed‐effects and Cox proportional‐hazard models. Cross‐lagged panel models were used in specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In the present study, we chose to use one set size (i.e. 3) for the sake of comparability of findings along the disease continuum, particularly considering our aim of anticipating the MCI stages [ 9 , 23 , 63 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we chose to use one set size (i.e. 3) for the sake of comparability of findings along the disease continuum, particularly considering our aim of anticipating the MCI stages [ 9 , 23 , 63 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…[11,82]). A growing number of studies are reporting cognitive deficits in subthreshold [33,63,75,83,84] and subclinical [71,73,79] stages of the disease continuum. The former evidence comes from studies using Aβ markers in the brain, CSF or blood [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Subtle cognitive impairment already exists when AD pathology starts accumulating in the brain at detectable thresholds. 5,6,12,41,47,48 Subthreshold levels of -amyloid PET imaging were associated with a decline in FR scores in the A4 study. 20 FR was most sensitive to -amyloidrelated decreases in average cognitive scores, outperforming all tests including logical memory.…”
Section: Discussionmentioning
confidence: 86%
“…4 There is increasing evidence that a subset of cognitively normal individuals has subtle cognitive impairment at baseline. [5][6][7] Not all cognitively normal, biomarker-positive individuals clinically progress to cognitive impairment over the typical duration of a clinical trial, say 18-36 months. 8,9 Because the objective of treatment in many clinical trials is to slow the rate of cognitive decline, inclusion of individuals unlikely to decline, even if randomized to placebo, will attenuate power to identify treatment effects in trials.…”
mentioning
confidence: 99%
“…Several studies have already shown that cognitively unimpaired individuals with MNPD, operationalized with differing criteria and cut-offs, have an increased risk of AD biomarker abnormalities [24][25][26] and progression to MCI or dementia [24][25][26][27] as well as increased brain atrophy 27,28 compared with those without MNPD. However, few studies have investigated the effect of MNPD in older individuals with SCD and those that did focused solely on cross-sectional biomarker analyses.…”
Section: Discussionmentioning
confidence: 99%